1977
DOI: 10.1111/j.1365-2672.1977.tb00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Spore Specific Antigens in Ultrathin Sections

Abstract: It has been demonstrated, using immunocytochemical techniques, that individual spore antigens are synthesized in discrete compartments of the bacterial cell. An outer layer of bacterial spores, demonstrable ultrastructuraby as a distinct exosporium in Bacillus cereus or as an outer tightfitting sporecoat in 8. subfilis, is synthesized in the cytoplasm of the mother cell. Conversely, the layers of the inner sporecoat antigens are synthesized in the forespore compartment and in association with the forespore mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

1980
1980
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(21 reference statements)
2
5
1
Order By: Relevance
“…The distribution of radioactivity in the forespore (Table 2) and the analysis of the membranous-soluble protein on the SDS-polyacrylamide gel (Fig. 5) confirm the results of Short et al (21). These results also imply that coat components (mainly the low-molecular-weight polypeptides) synthesized in the forespore compartment are probably transported across the cortex and two unit membranes of the forespore during assembly of the spore coat layer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The distribution of radioactivity in the forespore (Table 2) and the analysis of the membranous-soluble protein on the SDS-polyacrylamide gel (Fig. 5) confirm the results of Short et al (21). These results also imply that coat components (mainly the low-molecular-weight polypeptides) synthesized in the forespore compartment are probably transported across the cortex and two unit membranes of the forespore during assembly of the spore coat layer.…”
Section: Discussionsupporting
confidence: 86%
“…A recent immunocytochemical study indicates that the outer layer of the spore coat in B. cereus and B. subilis is synthesized in the mother-cell cytoplasm, and that, conversely, the inner layer of the spore coat is synthesized in the forespore compartment (21). Electron microscopic observation indicated that the t5 forespore of B. subtilis 60015 is at an early stage V and has a normal morphology of the cortex layer and immature spore coat layers.…”
Section: Discussionmentioning
confidence: 99%
“…protein, the precursor may be very easily extracted from the forespores during isolation procedures. The only previously published evidence for the site of spore-coat synthesis reported immunocytochemical localization of purified coatspecific antigen within the forespore compartment (Short et al, 1977). The spore-coat material used for antibody preparation in this latter study still contained the spore outer membrane, which forms part of the integument fraction (Crafts-Lighty & Ellar, 1980), and the possibility exists therefore that the antiserum was preferentially directed towards forespore-specific membrane proteins rather than the structural components of the spore coat that are under examination in the present paper.…”
Section: Pulse For 5min With L-[35slmethionine At Stage V and Subsequmentioning
confidence: 99%
“…A little more DPA found in the coat region, which cannot be overlooked, may correspond to a completely dissociated form of DPA which is released in small amounts during heat activation (5,18). Short et al (20) also observed small deposits of DPA in the coat region of B. cereus dormant spores stained with DPA-conjugated antiserum and peroxidase-antiperoxidase, but they regarded them as negligible. More deposits of DPA in the coat region of autoclaved spores seem to be caused by a flux of DPA located in the core, owing to the unusual heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…24showed DPA to be located in the cortical region, particularly just beneath the spore coat. Subsequently, however, they reported, by the use of the soluble peroxidase-antiperoxidase complex and unlabeled antibody to DPA, that DPA is located predominantly in the core of mature spores (20). Beta-attenuation analysis (11) and UV irradiation (2) have suggested that DPA is located primarily in the spore core.…”
mentioning
confidence: 99%